I testimoni del XIV secolo del "Pluto" di Aristofane - Cisterna, Domenica Maria (Premio Ricerca «Città di Firenze», 2012)
Among the almost 200 copies containing Plutus, the 23 fourteenth-century codices analysed in the book are the most ancient after the vetustiores and their collation has enabled the construction of a stemma codicum which effectively represents the Byzantine scholars' study environments and how they intersect. The identification of a Tzetzian study circle, which must have drawn from ancient sources, has led to an understanding of the nature of a large part of the fourteenth-century testimonies, thereby avoiding the generic explanation of contaminatio. This work makes further, interesting contributions through its recognition of the characteristics of the "Thoman" edition and identification of a link between Thessalonica and Constantinople, and also has the merit of having created greater clarity in the complex and as yet unstudied tradition of Plutus.